(untitled) (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
Surveillance technologies – CCTV networks, biometric identification systems, smart city sensors, and workplace monitoring platforms – create acute tensions between legitimate security objectives and fundamental privacy rights. Privacy-aware system architectures embed privacy constraints directly into surveillance infrastructure design, enabling security functions while providing formal privacy protections that policy controls alone cannot guarantee. This paper proposes the Privacy-Aware Surveillance Architecture Framework (PASAF), evaluating five architectural approaches – privacy-by-design, data minimisation architecture, purpose-limitation enforcement, federated surveillance processing, and zero-knowledge verification – across four surveillance domains: public space monitoring, workplace analytics, border control AI, and smart city infrastructure. PASAF introduces the Privacy-Security Balance Score (PSBS) integrating formal privacy guarantee strength, security utility preservation, GDPR compliance completeness, and proportionality. Key results: federated surveillance processing achieves the highest PSBS (0.892), preserving 94.8% of security utility at strong formal privacy guarantees; zero-knowledge verification achieves exact security function with no data exposure; data minimisation architecture reduces re-identification risk by 84.2% vs. conventional centralised surveillance. The framework provides architecture selection guidance for privacy-compliant surveillance deployment.